TATTWA TANPA PRAKTIK: FENOMENA DISORIENTASI NILAI PENDIDIKAN AGAMA HINDU DI KALANGAN GENERASI MUDA - Ni Kadek Novia Sri Wahyuni (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
This study aims to analyze the phenomenon of value disorientation in Hindu religious education among the younger generation through the concept of “tattwa without practice” in the digital era. The study is motivated by the tendency of Hindu youth to understand tattwa teachings conceptually but fail to implement these values in their daily lives. This research employed a qualitative approach with a descriptive-critical design. Data were collected through observation, in-depth interviews, and documentation studies involving Hindu youth, Hindu religious education teachers, religious leaders, and community members. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. The findings reveal that the phenomenon of “tattwa without practice” is influenced by digital culture, weakened internalization of religious values, the dominance of cognitively oriented religious education, and the declining role of family and social environments in shaping the religious character of young people. Social media has transformed youth religiosity into a more symbolic, performative, and pragmatic form, causing Hindu values to be understood more as cultural identity than as moral and spiritual guidance. This study emphasizes that the revitalization of Hindu religious education should focus on strengthening the integration between tattwa, susila, and social praxis through contextual, reflective, and experiential learning approaches. Therefore, Hindu religious education is expected to produce a younger generation who not only understand religious teachings theoretically but are also able to implement dharmic values in social life within the digital era.